Performance optimization and mechanism study of asphalt mixtures modified with ZM additive - Yining Wang; Weishuai Ji (PLoS ONE, 2025)
To enhance the high-temperature stability, low-temperature crack resistance, moisture susceptibility, and fatigue life of asphalt mixtures, this study systematically investigates the effects of Zhongmao Modifier (ZM), a solid granular direct-to-asphalt polymer–resin additive produced by Zhongmao Company (Shenyang, China), dosage and mixing process parameters on the pavement performance of asphalt mixtures and elucidates the underlying mechanisms. Orthogonal experiments determined the optimal mixing parameters as a mixing temperature of 170°C, dry mixing time of 180 s, and wet mixing time of 240 s. Experimental results show that the ZM modifier significantly improves the dynamic stability and rutting resistance of the mixture, with dynamic stability increasing to 5245 and rut depth decreasing to 2.26 mm at a dosage of 0.5%. The low-temperature flexural strain increases while the bending stiffness decreases, indicating improved crack resistance. In terms of moisture stability, both the retained stability and freeze–thaw splitting strength ratio outperform those of the base asphalt, reaching 88% and 90%, respectively. Fatigue test results reveal that the ZM modifier markedly extends fatigue life, with a maximum increase of 128.9%, and reduces fatigue sensitivity to the stress ratio. Displacement evolution analysis indicates that the modifier enhances inter-aggregate bonding, increases failure displacement, prolongs the stable phase, and significantly improves overall durability. Mechanistic analysis suggests that the polymer–resin components of the ZM modifier form a stable elastic network within the asphalt matrix and strengthen the interfacial bonding between asphalt and aggregates, thereby improving high-temperature stability and durability while maintaining low-temperature flexibility. The findings provide theoretical support and practical guidance for the broader application of ZM-modified asphalt mixtures in real-world pavement engineering, particularly for enhancing the performance and service life of road surfaces under varying environmental conditions.